Multiple subtropical stratospheric intrusions over Reunion Island: Observational, Lagrangian, and Eulerian numerical modeling approaches. Issue 24 (22nd December 2016) - Vérèmes, H.; Cammas, J.‐P.; Baray, J.‐L.; Keckhut, P.; Barthe, C.; Posny, F.; Tulet, P.; Dionisi, D.; Bielli, S.
Abstract: Signatures of multiple stratospheric intrusions were observed on simultaneous and collocated ozone and water vapor profiles retrieved by lidars and radiosondes at the Maïdo Observatory, Reunion Island (21°S, 55°E, 2160 m above sea level), during MAïdo LIdar Calibration CAmpaign in April 2013. A singular structure of the ozone vertical profile with three peaks (in excess of 90 ppbv, at ~8, ~10, and ~13 km altitude) embedded in a thick dry layer of air suggested stratospheric intrusions with multiple origins. The hypothesis is corroborated by a synoptic analysis based on re‐analyses. European Centre for Medium‐Range Weather Forecasts ERA‐Interim temporal series associated with 5 days Lagrangian back trajectories initialized on each ozone peak allows to capture their stratospheric origin. The ozone peak at the lowest altitude is associated with an irreversible tropopause folding process along the polar jet stream during an extratropical cutoff low formation. Simultaneous lidar water vapor profiles of this peak show that the anticorrelation with ozone has been removed, due to mixing processes. Back trajectories indicate that the two other ozone peaks observed at higher altitudes are associated with the dynamics of the subtropical jet stream and the lower stratosphere. The observations confirm the recent stratospheric origins. The highest ozone peak is explained by the horizontal distribution of the intrusion. Use of a Lagrangian Reverse Domain Filling model and of the Meso‐NH Eulerian mesoscale model with a passive stratospheric tracer allow to further document the stratosphere‐troposphere transport processes and to describe the detailed potential vorticity and ozone structures in which are embedded in the observed multiple stratospheric intrusions. Key Points: Ozone and water vapor lidar observations of a multiple stratospheric intrusion events over Reunion Island Reconstruction of the 3‐D structures of stratospheric air masses in the upper troposphere Eulerian and Lagrangian models' ability to simulate realistically a multiple stratospheric intrusions process